دور القيادة التحويلية في تعزيز الولاء لدى الموظفين في المؤسسة الاقتصادية - مريم زعفور; هنادي جواد (My University, 2024)
This study aimed to identify the extent to which transformational leadership contributes in its various dimensions (ideal influence, inspirational motivation, intellectual stimulation, and individual considerations). In enhancing loyalty among employees at the economic institution Sonelgaz (National Electricity and Gas Distribution Company - Souk Ahras). For this purpose, a questionnaire list was designed, consisting of42 statements, and a comprehensive survey method was used to collect data from the study population. The questionnaire list was distributed to all employees in this institution, where42 questionnaires were distributed, of which 42 questionnaires were returned, suitable for statistical analysis, i.e.100 of the questionnaires. Total community size. This% study relied on the descriptive analytical approach and the field study method to collect the necessary data (SPSS) to complete it, and relied on statistical software for the social sciences. In analyzing the study data and testing its hypotheses, descriptive statistics were used to present questionsThe study also used normal distribution tests and simple regression analysis to test its hypotheses.The study reached a set of results, the most notable of which are: _ There are characteristics of transformational leadership among presidents in the field of study, _ Transformational leadership in its various dimensions contributes significantly to enhancing and achieving loyalty among employees in the organization, _ The employees of the organization also enjoy a moderate degree of loyalty, _ There is a significant effect Statistics for transformational leadership and loyalty among employees in the organization. هدفت هذه الدراسة للتعرف الى مدى اسهام القيادة التحويلية بأبعادها المختلفة (التأثير المثالي، التحفيز الا لهامي، الاستثارة الفكرية، الاعتبارات الفردية). في تعزيز الولاء لدى الموظفين في المؤسسة الاقتصادية سونلغاز (الشركة الوطنية لتوزيع الكهرباء والغاز _سوق أهراس). ولهذا الغرض تم تصميم قائمة استبيان تكونت من 44 عبارة، وتم استخدام أسلوب المسح الشامل لتجميع البيانات من مجتمع الدراسة، وقد وتم توزيع قائمة الاستبيان على جميع الموظفين في هذه المؤسسة، حيث تم توزيع42 استبيانا استرد منها 42استبيانا صالحا للتحليل الاحصائي أي ما نسبته 100% من حجم المجتمع الكلي ،وقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي وأسلوب الدراسة الميدانية لجمع لبيانات الازمة لإتمامها، وتم الاعتماد على البرمجيات الإحصائية SPSS للعلوم الاجتماعيةفي تحليل بيانات الدراسة واختبار فرضياتها، حيث تم استخدام الإحصاء الوصفي لعرض أسئلة الدراسة، كما تم استخدام اختبارات التوزيع الطبيعي وتحليل الانحدار البسيط لاختبار فرضياتها. وقد توصلت الدراسة الى مجموعة من النتائج من أبرزها: _ توجد سمات القيادة التحويلية لدى الرؤساء بميدان الدراسة، _ان القيادة التحويلية بأبعادها المختلفة تساهم بشكل معنوي في تعزيز وتحقيق الولاء لدى الموظفين في المؤسسة، _كما يتمتع العاملين بالمؤسسة بدرجة متوسطة من الولاء، _وجود تأثير ذو دلالة إحصائية للقيادة التحويلية والولاء لدى الموظفين بالمؤسسة. Cette étude visait à identifier dans quelle mesure le leadership transformationnel contribue dans ses différentes dimensions (influence idéale, motivation inspirante, stimulation intellectuelle et considérations individuelles). Dans la fidélisation des employés de l'institution économique Sonelgaz (Société nationale de distribution d'électricité et de gaz - Souk Ahras). À cette fin, une liste de questionnaires a été conçue, composée de 42 énoncés, et une méthode d'enquête complète a été utilisée pour recueillir des données auprès de la population étudiée. La liste des questionnaires a été distribuée à tous les employés de cette institution, où 42 questionnaires ont été distribués, dont 42 questionnaires ont été retournés, adaptés à l'analyse statistique, soit 100 questionnaires. Taille totale de la communauté. Cette étude s'est appuyée sur l'approche analytique descriptive et la méthode d'étude de terrain pour collecter les données nécessaires (SPSS) pour la compléter, et s'est appuyée sur des logiciels statistiques pour les sciences sociales. L'étude a également utilisé des tests de distribution normaux et une analyse de régression simple pour tester ses hypothèses. L'étude a abouti à une série de résultats, dont les plus notables sont les suivants : _ Il existe des caractéristiques du leadership transformationnel chez les présidents dans le domaine d'étude, _ Le leadership transformationnel dans ses différentes dimensions contribue de manière significative à améliorer et à atteindre la loyauté des employés de l'organisation, _ Les employés de l'organisation bénéficient également d'un degré modéré de loyauté, _ Il y a un effet significatif Statistiques pour le leadership transformationnel et la loyauté parmi les employés de l'organisation.
Keywords: Keywords: Transformational leadership and its dimensions (exemplary impact; inspirational motivation; intellectual arousal; individual considerations) Job loyalty; Sonelgaz Foundation.; الكلمات المفتاحية: القيادة التحويلية وأبعادها (التأثير المثالي، التحفيز الإلهامي، الإستثارة الفكرية، الإعتبارات الفردية) الولاء الوظيفي، مؤسسة سونلغاز.; Mots-clés : Le leadership transformationnel et ses dimensions (impact exemplaire; motivation inspirante; éveil intellectuel; considérations individuelles) Fidélité au travail; Fondation Sonelgaz.